10Be dating reveals early-middle Holocene age of the Drygalski Moraines in central West Greenland - Sandra L. Cronauer; Jason P. Briner; Samuel E. Kelley; Susan R.H. Zimmerman; Mathieu Morlighem (Quaternary Science Reviews, 2016)
Abstract We reconstruct the history of the Greenland Ice Sheet margin on the Nuussuaq Peninsula in central West Greenland through the Holocene using lake sediment analysis and cosmogenic 10Be exposure dating of the prominent Drygalski Moraines. Erratics perched on bedrock outboard of the Drygalski Moraines constrain local deglaciation to ∼9.9 ± 0.6 ka (n = 2). Three Drygalski Moraine crests yield mean 10Be ages of 8.6 ± 0.4 ka (n = 2), 8.5 ± 0.2 ka (n = 3), and 7.6 ± 0.1 ka (n = 2) from outer to inner. Perched erratics between the inner two moraines average 7.8 ± 0.1 ka (n = 2) and are consistent with the moraine ages. Sediments from a proglacial lake with a catchment area extending an estimated 2 km beneath (inland of) the present ice sheet terminus constrain an ice sheet minimum extent from 5.4 ka to 0.6 ka. The moraine chronology paired with the lake sediment stratigraphy reveals that the ice margin likely remained within ∼2 km of its present position from ∼9.9 to 5.4 ka. This unexpected early Holocene stability, preceded by rapid ice retreat and followed by minimum ice extent between ∼5.4 and 0.6 ka, contrasts with many records of early Holocene warmth and the Northern Hemisphere summer insolation maximum. We suggest ice margin stability may instead be tied to adjacent ocean temperatures, which reached an optimum in the middle Holocene.
Special Issue: \{PAST\} Gateways (Palaeo-Arctic Spatial and Temporal Gateways)
Keywords: Holocene